Lohrli Revisited: Newly Identified Contributors to Household Words. - Parrott, Jeremy (Dickens Quarterly, 2018)
The article reports on the newly identified contributors to the journal "Household Words" written by Anne Lohrli and conducted by English author Charles John Huffam Dickens. Topics discussed include surname Rolfes recorded in 1861 Great Britain census data, Edwin Roffe (1825–91), who produced engravings of Dickens's parents and his wife Catherine and contents of Victorian periodical "All the Year Round."